2021
DOI: 10.1111/odi.13814
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HPV and EBV in OSCC and the expression of p53, p16, E‐cadherin, COX‐2, MYC, and MLH1

Abstract: Objective This study aimed to evaluate the presence of human papillomavirus (HPV) and Epstein–Barr virus (EBV) and the expression of p53, p16, E‐cadherin, COX‐2, MLH1, and MYC in oral squamous cell carcinoma (OSCC). Materials and Methods One hundred OSCC specimens were submitted to in situ hybridization for HPV and EBV, and immunohistochemistry for detection of the human proteins. Results Thirty‐one cases showed HPV in tumor tissue. EBV was not detected in any case investigated. The HPV(+) group demonstrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 182 publications
(330 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, it has been speculated that the p16 concentration could be higher in OSCC patients with HPV infection [ 53 ]. The correlation is attributed to the effect of the viral protein E7 that is able to inhibit tumour suppressors, particularly Rb1 protein, which could result in an increased p16 level [ 47 , 54 ]. Consequently, multiple studies have attempted to evaluate the utility of p16 as a surrogate marker for HPV infection in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been speculated that the p16 concentration could be higher in OSCC patients with HPV infection [ 53 ]. The correlation is attributed to the effect of the viral protein E7 that is able to inhibit tumour suppressors, particularly Rb1 protein, which could result in an increased p16 level [ 47 , 54 ]. Consequently, multiple studies have attempted to evaluate the utility of p16 as a surrogate marker for HPV infection in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Staining of tissue sections showed that FAM3B expression decreased in OSCC tissues. Mouse experiments showed that knockdown of FAM3B promotes cell apoptosis by upregulating p53 in mice [ 27 ], and the expression of p53 protein increases in OSCC [ 28 ]. Therefore, FAM3B might cause OSCC by upregulating p53 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Although P53 protein is targeted by E6 and degraded in many cancers, this protein was not reduced in OSCCs in a number of studies. The justification for this event states that because of the increase in mutant p53 in HPV-negative OSCC patients, as well as the fact that this event occurs prior to HPV infection, E6 loses its ability to bind to this mutated protein and cannot degrade it [ 105 ].…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…Although the results regarding the expression of P16 in HPV-positive OSCC patients are contradictory, an increase in the expression of this protein has been reported in several studies as a result of Rb suppression by E7. As a result, this increased expression suggests a strong link between HPV infection and the presence of P16, which has been proposed as a surrogate marker for HPV-HR in a number of cancer studies [ 105 – 107 ]. c-MYC and MLH1 were other genes targeted by the HPV in this cancer, which have been reported to increase and decrease their expression, respectively.…”
Section: Head and Neck Cancermentioning
confidence: 99%
See 1 more Smart Citation